2023
DOI: 10.1590/1806-9282.20220493
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of toxin-antitoxin genes, antibiotic resistance, and virulence genes in Pseudomonas aeruginosa isolates

Abstract: OBJECTIVE: Toxin-antitoxin genes RelBE and HigBA are known to be involved in the formation of biofilm, which is an important virulence factor for Pseudomonas aeruginosa. The purpose of this study was to determine the presence of toxin-antitoxin genes and exoenzyme S and exotoxin A virulence genes in P. aeruginosa isolates and whether there is a relationship between toxin-antitoxin genes and virulence genes as well as antibiotic resistance. METHODS: Identification of the isolates and antibiotic susceptibilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…For instance, Coskun and colleagues reported that Pseudomonas aeruginosa and Staphylococcus isolates sensitive to gentamicin, ciprofloxacin, levofloxacin, clindamycin, phosphomycine, nitrofurantoin, fusidic acid, cefoxitin expressed relatively higher levels of the mazEF gene compared with those of the resistant isolates [ 11 ]. Based on the findings of a more recent report by Coşkun and colleagues, P. aeruginosa isolates sensitive to imipenem and meropenem expressed significantly higher levels of the relBE gene while isolates sensitive to amikacin significantly expressed higher levels of the higBA gene [ 13 ]. Regarding A. baumannii , Ghafourian and colleagues reported that the mazEF gene was expressed by 85 clinical isolates and that this TA system-related expression should be further investigated as an antibacterial therapeutic strategy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Coskun and colleagues reported that Pseudomonas aeruginosa and Staphylococcus isolates sensitive to gentamicin, ciprofloxacin, levofloxacin, clindamycin, phosphomycine, nitrofurantoin, fusidic acid, cefoxitin expressed relatively higher levels of the mazEF gene compared with those of the resistant isolates [ 11 ]. Based on the findings of a more recent report by Coşkun and colleagues, P. aeruginosa isolates sensitive to imipenem and meropenem expressed significantly higher levels of the relBE gene while isolates sensitive to amikacin significantly expressed higher levels of the higBA gene [ 13 ]. Regarding A. baumannii , Ghafourian and colleagues reported that the mazEF gene was expressed by 85 clinical isolates and that this TA system-related expression should be further investigated as an antibacterial therapeutic strategy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…These systems belong to the type II TA systems. Among the TA systems found in A. baumannii, three genes, namely mazEF, relBE, and higBA, are the most investigated and important ones that belong to the type II TA system [5,7,[11][12][13][14]. Previous investigations have studied the relationship between these genes and antibiotic resistance and have asserted that further investigations are necessary.…”
Section: Introductionmentioning
confidence: 99%